V-energy : bio disc & chi pendant - Lyons, Ian; VStudios ([S.l.] : VStudios, 2008)
This video showcases Ian Lyons in a series of demonstrations proving and illustrating the components and wondrous possibilities can be achieved by the Biodisc and the Chi pendant. The instructional video also clarifies myths and misconceptions about the products
Title from title screen
DVD format
Keywords: Multilevel marketing; Direct marketing